Recent Advances on Quantum Key Distribution Overcoming the Linear Secret Key Capacity Bound. Issue 1 (25th November 2020) - Mao, Yingqiu; Zeng, Pei; Chen, Teng‐Yun
Abstract: A crucial goal for quantum key distribution (QKD) is to transmit unconditionally secure keys over long distances. Previous studies show that the key rate of point‐to‐point QKD is limited by a secret key rate capacity bound, and higher key rates would require quantum repeaters. In 2018, the seminal twin‐field (TF) QKD protocol is proposed to provide a remarkable solution to overcoming the linear secret key capacity bound. This article presents an up‐to‐date survey on recent developments in this area, including the security proofs of phase‐matching QKD and other TF‐QKD type protocols, the theoretical examinations of these protocols under realistic conditions, and the recent experimental demonstrations. Abstract : This article presents an up‐to‐date survey on recent developments on quantum key distribution (QKD) overcoming the linear secret key capacity bound, including the security proofs of twin‐field (TF) QKD, phase‐matching QKD, and other TF‐QKD type protocols, the theoretical examinations of these protocols under realistic conditions, and the recent experimental demonstrations.